1997
DOI: 10.1016/s0014-5793(97)01178-2
|View full text |Cite
|
Sign up to set email alerts
|

How melatonin interacts with lipid bilayers: a study by fluorescence and ESR spectroscopies

Abstract: ESR spectra of spin labels placed at the membrane surface and at different depths of the bilayer core, and melatonin fluorescence in the presence of lipid vesicles, suggest an average shallow position for the hormone in the membrane. However, according to the melatonin ability to cross lipid bilayers, nitroxides placed deep in the bilayer were able to quench the melatonin fluorescence. Melatonin membrane partition coefficients were calculated for bilayers in different packing states, and similar and rather hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
77
1
3

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(85 citation statements)
references
References 20 publications
4
77
1
3
Order By: Relevance
“…Since then, hundreds of publications have confirmed this observation [18,19]. As a free radical scavenger melatonin exhibits several important properties: (1) It is both lipophilic and hydrophilic [20,21] and it passes all bio-barriers, e.g., blood-brain barrier and placenta, with ease. It is available to all tissues and organs, even those in the fetus [22].…”
Section: Melatoninmentioning
confidence: 94%
“…Since then, hundreds of publications have confirmed this observation [18,19]. As a free radical scavenger melatonin exhibits several important properties: (1) It is both lipophilic and hydrophilic [20,21] and it passes all bio-barriers, e.g., blood-brain barrier and placenta, with ease. It is available to all tissues and organs, even those in the fetus [22].…”
Section: Melatoninmentioning
confidence: 94%
“…Unlike some other wellknown antioxidants that are exclusively lipid (e.g., vitamin E) or water (e.g., vitamin C) soluble and, therefore, exhibit a limited intracellular distribution, melatonin is amphiphilic allowing it to reduce dOH-mediated damage in both the lipid and aqueous subcellular compartments. Evidence has shown that melatonin is clearly highly soluble in a lipid-based medium (Costa et al 1997) and it has also been shown to dissolve in aqueous media (Shida et al 1994). Rather little is known concerning melatonin' s speci® c intracellular distribution or concentration, although the few studies that have been performed suggest that its deposition in diOE erent subcellular compartments is not Figure 3 In a pure chemical system, melatonin has been shown to directly interact with hydrogen peroxide (H 2 O 2 ) with the formation of N 1 -acetyl-N 2 -formyl-5-methoxykynuramine(AFMK).…”
Section: Melatonin : Direct Scavenging Actionsmentioning
confidence: 99%
“…For example, ·-tocopherol (vitamin E) and ascorbic acid (vitamin C) are exclusively soluble in lipid and aqueous media, respectively; thus, their direct free-radical-scavenging activity is limited to those portions of the cell in which they are located. On the other hand, while melatonin is highly lipid soluble [14], it has considerable aqueous solubility [15] as well. As a consequence, it is able to function as an antioxidant in virtually all parts of the cell and to protect membrane lipids, cytosolic proteins and nuclear DNA from oxidative damage [6].…”
Section: Melatonin and Antioxidant Defensementioning
confidence: 99%